Faktor-Faktor yang Memengaruhi Pencegahan Fraud dengan Budaya Organisasi sebagai Variabel Moderasi - Stiawati, Stiawati; Hidayatulloh, Amir (Jurnal Manajemen Bisnis dan Keuangan, 2024)
Fraud is a serious issue that can threaten the stability and reputation of an organization, including financial institutions like banks. Therefore, fraud prevention is crucial. This research examines how compensation appropriateness and whistleblowing system in influencing fraud prevention at Bank ABC. Additionally, this research aims to evaluate whether organizational culture can act as a moderator in this relationship. The research sample consists of 35 employees of Bank ABC, selected using a convenience sampling technique. Data were collected through the direct distribution of questionnaires to the respondents. Data analysis was conducted using IBM SPSS Statistics 29. The analysis results indicate that both compensation appropriateness and the whistleblowing system had a significant impact on fraud prevention. In addition, organizational culture was found to act as a moderating variable that affects the relationship between the whistleblowing system and fraud prevention. However, organizational culture does not moderate the relationship between compensation appropriateness and fraud prevention within Bank ABC. These findings suggest that both compensation appropriateness and the whistleblowing system have a significant impact on fraud prevention. While organizational culture plays an important role in enhancing the effectiveness of the whistleblowing system, it does not moderate the relationship between compensation appropriateness and fraud prevention.